Kıbrıs sorununun tarihsel gelişimi ve Avrupa Birliği'ne giriş sürecinde Türk Yunan ilişkilerine stratejik yaklaşımlar - Koç, Süleyman (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2004)
44 yıldır Kıbrıs meselesinde bir uzlaşma sağlanamamasının başlıca nedeni, " Uluslar arası camia" diye tabir edilen ABD ve İngiltere gibi güçlü ve etkili devletlerin, kendi ülkesel çıkarları nedeniyle Kıbrıs konusuna doğru bir teşhis koymaktan bu güne kadar kaçınmış olmalarıdır. Meselenin haline yardımcı olmak isteyen çevrelerin önce Kıbrıs meselesinin ne olduğunu araştırmaları ve iyice irdelemen gerekir. Kıbrıs meselesinin ne olduğunu, nasıl ortaya çıktığını Güney Rum lideri Glafkos Klarides " My deposition" adı altında yayınladığı kitabında kendisi vurgulamaktadır. Klaries, söz konusu kitabının 3' üncü cilt 105' inci sayfasında şunları yazmaktadır ° Kıbrıs Rumlarının amacı, adayı Türklerin koruma altına alınacakları bir Rum Cumhuriyeti' ne dönüştürmekti Türklerin tüm çabası ise antlaşmalarla kendilerine tanınan hakları müdafaa etmekti.... Durum bu günde aynıdır ve değişen bir şey yoktur." Rumlar, ulusal bir hedef olarak belirledikleri " Kıbrıs'ı bir Rum Cumhuriyeti'ne dönüştürme ve Yunanistan' la birleştirme (ENOSİS) " Hedefine ulaşmak gayesiyle iki halkın eşit kurucu ortaklığına dayalı 1960 ortaklık cumhuriyetini, aralık 1963' de Türklere karşı giriştikleri etnik temizlik operasyonu sonucunda silahlı saldırılarla yıktılar. Türkleri ortaklık cumhuriyetinin tüm organlarından dışladılar ve ana yasanın "Ölmüş ve gömülmüş" olduğunu ilan ettiler. Rum papaz Makarios 1963-1974 yıllarında Kıbrıs Türklerine etnik temizlik uygulamakla, Balkanları kan gölüne çeviren Sırp canilerin lideri Miloseviç' in bir anlamda öğretmenliğini yapmıştır. İki kurucu halkın eşit siyasi oraklığına dayanan 1960 Kıbrıs Cumhuriyetini, adayı bir Rum Cumhuriyetine dönüştürmek maksadıyla kasıtlı olarak yıkan Rumlar, Kıbrıs meselsini yaratan suçlu taraf olmalarına rağmen, Birlemiş Milletler Güvenlik konseyine tarafından 4 mart 1964' de alınan ve adaya Barışif *A t?

The main reason for not finding reconciliation (solution) for a period of 44 years in the Cyprus matter is the fact of refraining by the United States of America and England termed as "International community states" having power and influence as states, to define the matter of Cyprus in a correct manner because of interests of their countries. The communities who want to assist solving the matter must first enter into research to determine if what is the matter and it must be well analyzed. Southern Cyprus Greek Leader Glafkos Klarides, himself, in his book titled "My Deposition" emphasizes what are the facts of the matter in Cyprus and how it was faced. On page 105 of volume 3 of the subject book, Klarides, writes as follows: "The objective of Cyprus Greeks, is to convert the island into a Greek Republic where Turkey will be taken under protection. Whereas all of the efforts of Turks were to defend the rights grated to them with agreements...Today the things are the same and there is nothing changed". Greeks, determined it as a national target to "convert Cyprus into a Greek Republic and merge it with Greece (ENOSIS)" and to reach at this target, they have attached with arms to make a ethnic clearance operation against Turkey in the month of December of he year 1963 and demolished the 1960 associate republic basing on equal partnership of two people. They have pushed Turks out of all of the organs of the joint republic of association and announced that this constitution is "dead and buried". Greek chaplain Makarios during the years 1963-1974, applied ethnical clearing off of Cyprus Turks, and in a sense, acted as a teacher to the Serbia criminals leader Misoseviç who put Balkans into a state of a lake of blood. The 1960 Cyprus Republic basing on equal political association of two founder people, with the purpose of converting the island into a Greek Republics, demolished the Republic on purpose, were the offender party/* - "^^>^ ^ creating the Cyprus matter but in the resolution oft he United Nations Security council dated 4 March 1964 and contemplating placement of Peace Force to the island, without having any right and by being contrary to the international norms, they were accepted as the legitimate government of Turkish Cyprus". Makarios in his will stated for the Greek leaders to assume power after him, had said; "by having Greeks accepted as the legitimate government I have brought Cyprus to the closest position to the ENOSIS. Regardless of what it is do not ever move back from this title, at what ever cost it may be... If you are to move back, move back only for ENOSIS!". Therefore, the United Nations Security Council unjustly considered them as the "Legitimate government" and thus the Greek side is in the opinion that they have reached the target they desired to reach and the basic political policy followed, was determined as "not to abandon this title for what ever cost it may have" to have Peace Force forwarded to the island. Having Greeks accepted under this false title, did not leave any desire and motivation even the smallest one at the Greek side to act in the direction of solving the matter faced. This is also the basic reason for not attaining any reconciliation for a period of 44 years in the Cyprus matter. After the Greek cope the etat of 1974 forming the last step taken in the path of realization of ENOSIS, Turkey by using the legitimate right of defense based on guarantor ship agreements, saved Turks of Cyprus from being massacred. With the population exchange agreement of 1975, being in two sections in the island was attained. As a result of irreconcilable attitude of Greek side, within the good will mission of United Nations, since 1977, until 1983, there were negotiations entered into and there were no results attained. Upon this, the Turks of Cyprus, on 15 November 1983 declared their independent and sovereign state. In other words, the Northern Cyprus Turkish Republic was announced as founded.To arrive at reconciliation in Cyprus, the talks under observation of United Nations (UN) were continuing and on 3 July 1990 the Greek side, make application for membership to European Union. This one sided application of Greeks made contrary to the founders agreement, was based on not economic but political objectives. The objectives of Greeks to become a member in the European Union.was to discontinue the effective guaranty of Turkey registered with agreements over Cyprus and as an extension of 1923 Lozan Agreement, to disturb the Turkish-Greek balance attained in Cyprus in their favor at a single side. The European Union, despite rightful objections of the Turkish side of Cyprus, by accepting the application made by Greeks under the title of being the "Legitimate Government" and putting it into processing, increased the act of not getting reconciled further on the Greek side on the subject of Cyprus. The Greek side, by entering into the expectations that they will any way be reaching at the target desired by means of the membership in the European Union, turned their back to the solution parameters determined to that date. Thus "talks between the communities" and 'federal solution based on two sections" were efforts that were actually not shown. The Turkish side of Cyprus, following the 1 997 Luxembourg Summit where the decision to have membership talks started with Greeks assumed as the "only party to talk" by EU, stated that after this the negotiations can be done only by between the state to state. With our proposal put forward on 31 August 1998, it was disclosed that the target of the talks to be made between the two states will be confederation. However, the Greek side, with the effect of Greece too and by basing on the courage received from the EU membership process, immediately rejected the confederation proposals made by the Turkish side. ... Therefore, having EU to participate in Cyprus matter with the^e^pthat 'it will act as "catalyzing processes" pushed the greed side to a more courageous position in the direction of not getting reconciled and made the efforts to reconciliation more difficult as a thing arising contrary to the original thinking. Taking Greek side alone to the EU membership means indirectly having Greeks become integrated with Greece which is a member in the EU. Whereas, 1960 agreements, along with ENOSIS and division, banns Cyprus to become member in any international organization in which the two main land namely Turkey and Greece are not members together. The objective "was to not to give a chance to discontinue the independence of the state formed in 1 960 as the state of association in form of a state having "restricted authorizations". As a result of dense shuttle diplomacy entered into with both parties, in he "Arrays of Ideas" put into open by the UN in 1992, it was stated that the membership of Cyprus to EU could be approved to appear in the agenda on condition that the two people after an agreement arrange separate referendums. Despite the valid international agreements and all of these realities, the application made single side, by the Greek side to EU was accepted and put into processing and this is a shame for the humanity. The Greek side aware hat all of these conditions are operating in their favor, did not accept any solution proposal made to them at all and at the same time, as they have targeted, in the month of May of the year 2004, they became member of the European Union. Thus, the balance attained with 1960 agreements were changed in favor of Greece and Cyprus Greeks. Reconciliation in Cyprus can be possible only by making a correct formulation of the mater faced. The confederation proposal of the Turkish side of Cyprus, is the most logical, most realistic and applicable method that can be indicated. The Turkish side in Cyprus, after the painful experiences of past, are desiring to have a permanent agreement that can not be disobeyed again byXll Greeks at any time they so desire. For a probable agreement to be permanent and as it was in 1 963", for not to having it stay on the paper only, it must base on the state and the principle of sovereignty. Thus, in case the Greeks attack Turks of Cyprus in future, the crises to arise will not be possible to be introduced to outside world as done in the past as an "internal matter" and will be seen as an open attack of an sovereign state to another sovereign state.
The historical development of Cyprus issue and strategical approaches to Turkish-Greece relations in the process of entering EU
Keywords: Uluslararası İlişkiler; International Relations